Electric Vehicle Conversion Study for Sustainable Transport - Fuad Zainuri; Muhammad Hidayat Tullah; Sonki Prasetya; Iwan Susanto; Dewin Purnama; Rahmat Subarkah; Tia Ramiati; Widiyatmoko; Rahmat Noval (MBI, 2023)
The conversion of conventional motor vehicles to electric vehicles has become a popular choice in an effort to reduce greenhouse gas emissions and air pollution from transportation. Electric vehicle conversion involves replacing a gasoline or diesel engine with an electric motor and a reinstalled battery. In this paper, we cover the basics of electric vehicle conversion, conversion methods, and trial results of converted electric vehicles. We also discuss the benefits and challenges of converting to electric vehicles. Some keywords related to this topic include: electric vehicles, vehicle conversion, electric motors, batteries, sustainable transportation.